Mobergellans from the early Cambrian of Greenland and Labrador: new morphological details and implications for the functional morphology of mobergellans. (29th August 2017) - Skovsted, Christian B.; Topper, Timothy P.
Abstract: New morphological features of the mobergellan Discinella micans (Billings, 1871) from the lower Cambrian (Stage 4) of Northeast Greenland and southern Labrador are described. The new features include: (1) the morphology of the larval shell, which is shown to be cap-shaped, subcircular, and with impressions of the internal muscle attachment scars; (2) a range of unusual shell deformations (changes in growth direction resulting in thickened shells, partial detachment of shell laminae and subsequent regrowth, internal projections of shell material increasing the depth of the shell by up to 150%, disturbances and irregular fusion of muscle scars). In addition, we provide new details about the variability in number and shape of the anteriormost internal muscle scars, which often fuse and may vary in number from one to three (resulting in nine to 11 scars in total). Together the new observations provide additional strength for the hypothesis that mobergellan shells represent opercula of an as yet unknown tubular organism.